URANIUM(VI) IN AQUEOUS SOLUTIONS AT 25°C AND A PRESSURE OF 1 BAR: INSIGHT FROM EXPERIMENTS AND CALCULATIONS - Redkin A.F.; Wood S.A. (My University, 2007)
The behavior of the 0.1 mNaCl + 0.002 mHCl + 1.9 × 10-5 mUO2(NO3)2 solution was studied at pH from 2.7 to 11.0, 25°C, and 1 bar in an argon atmosphere. The curve of variations in U concentration exhibits two minima at pH = 6.6 ± 0.7 and 10.0 ± 0.5. These minima are related to the precipitation of schoepite and clarkeite, respectively. The experimental data were used to refine the stability constants of U(VI) (hydroxo) complexes. For the polymer species of U(VI) with charges from +2 to -1, the method of additivity of thermochemical increments was used, and increments of the linear relation were determined for the calculation of the Gibbs free energies of formation (Δf G298.150) of respective homologue series. The proposed method was applied to calculate the Δf G298.150 of formation of U(VI) (hydroxo)complexes containing from one to five uranium atoms. © Pleiades Publishing, Ltd. 2007.